Trading Market Access for Competition Policy Enforcement - Hoekman, Bernard; Saggi, Kamal (World Bank, Washington, D.C., 2013)
Motivated by discussions at the World Trade Organization (WTO) on multilateral disciplines with respect to competition law, the authors develop a two-country model that explores the incentives of a developing country to offer increased market access (by way of a tariff reduction) in exchange for a ban on foreign export cartels by its developed country trading partner. They show that such a bargain is feasible and can generate a globally welfare-maximizing outcome. The authors also explore the incentives for bilateral cooperation when the developing country uses transfers to "pay" for competition enforcement by the developed country. A comparison of the two cases shows that there exist circumstances in which the stick (the tariff) is more effective in sustaining bilateral cooperation than the carrot (the transfer). Furthermore, the scope for cooperation is maximized when both instruments are used. An implication of the analysis is that developing countries have incentives to support an explicit WTO prohibition of export cartels.